Everyday Life Emotions during Anti-Fugitive Offenders Ordinance Protests in Hong Kong - Ma, Tsz-Wah (European Journal of Mental Health, 2020)
This experience sampling study investigated the impact of political movement (i.e. Anti-FugitiveOffenders Ordinance Protests) on everyday emotional reactivity and dynamics. Participants whofinished our experience sampling during Movement (18–70 years; n = 100) and matched sample(18–70 years; n = 100) reported positive and negative emotions seven times a week for five weeks.Hierarchical linear modeling revealed that during the Movement, participants reported lower positiveemotions and higher negative emotions, and lower positive emotional inertia and higher nega -tive emotional inertia. This study is the first of its kind to investigate different aspects of everydayemotional experiences during political movements. Participants perceived significant changes intheir everyday events although the Movement was not long and not severely violent. This studyhighlights the importance of investigating everyday emotions of people in other more serious conflictand post-conflict settings.